The benefits of sacubitril–valsartan in patients with acute myocardial infarction: a systematic review and meta‐analysis. (30th October 2021) - Xiong, Bo; Nie, Dan; Qian, Jun; Yao, Yuanqing; Yang, Gang; Rong, Shunkang; Zhu, Que; Du, Yun; Jiang, Yonghong; Huang, Jing
Abstract: Aims: We aimed to investigate whether sacubitril–valsartan could further improve the prognosis, cardiac function, and left ventricular (LV) remodelling in patients following acute myocardial infarction (AMI). Methods and results: We searched the PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure (CNKI) from inception to 10 May 2021 to identify potential articles. Randomized controlled trials (RCTs) meeting the inclusion criteria were included and analysed. Thirteen RCTs, covering 1358 patients, were analysed. Compared with angiotensin‐converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB), sacubitril–valsartan did not significantly reduced the cardiovascular mortality [risk ratio (RR) 0.65, 95% confidence interval (CI) 0.22 to 1.93, P  = 0.434] and the rate of myocardial reinfarction (RR 0.65, 95% CI 0.29 to 1.46, P  = 0.295) of patients following AMI, but the rate of hospitalization for heart failure (HF) (RR 0.48, 95% CI 0.35 to 0.66, P  < 0.001) and the change of LV ejection fraction (LVEF) [weighted mean difference (WMD) 5.49, 95% CI 3.62 to 7.36, P  < 0.001] were obviously improved. The N‐terminal pro‐brain natriuretic peptide (NT‐ProBNP) level (WMD −310.23, 95% CI −385.89 to −234.57, P  < 0.001) and the LV end‐diastolic dimension (LVEDD) (WMD −3.16, 95% CI −4.59 to −1.73, P  < 0.001) were also significantly lower in sacubitril–valsartan group than in ACEI/ARB group. Regarding safety, sacubitril–valsartan did not increase the risk of hypotension, hyperkalaemia, angioedema, and cough. Conclusions: This meta‐analysis suggests that early administration of sacubitril–valsartan may be superior to conventional ACEI/ARB to decrease the risk of hospitalization for HF, improve the cardiac function, and reverse the LV remodelling in patients following AMI.